Transient and residual stresses induced during the sintering of two dentin ceramics. - FLEMING, GARRY (Elsevier, 2011)
Objective: The effect of heat-pressing and subsequent pre-cementation (acid-etching) and resin-cementation operative techniques on the development of transient and residual stresses in different thicknesses of a lithium disilicate glass-ceramic were characterised using profilometry prior to biaxial flexure strength (BFS) determination. Methods: 60 IPS e.max Press discs were pressed and divested under controlled conditions. The discs were polished on one surface to thicknesses of 0.61 ? 0.05, 0.84 ? 0.08, and 1.06 ? 0.07 mm (Groups A-C, respectively). The mean of the maximum deflection (acid-etching and resin-coating was determined using high resolution profilometery prior to BFS testing. Paired sample t-tests were performed (P < 0.05) on the 20 individual samples in each group (Groups A-C) for each comparison. Differences between the baseline quantification and resin-cement coating deflection values and BFS values for Groups A-C were determined using a one-way ANOVA with post-hoc Tukey tests (P < 0.05). Results: Baseline quantification for Groups A-C identified no significant differences between the group means of the maximum deflection values (p = 0.341). Following HF acid-etching, a significant increase in deflection for all groups (p < 0.001) was identified compared with the baseline quantification. Additionally, resin-cement coating significantly increased deflection for Group A (p < 0.001), Group B (p < 0.001) and Group C (p = 0.001) specimens for the individual groups. The increased deflection from baseline quantification to resin-cement coating was significantly different (p < 0.001) for the three specimen thicknesses, although the BFS values were not. Significance: The lower reported baseline quantification range of the mean of the maximum deflection for the IPS e.max? Press specimens was predominantly the result of specimen polishing regime inducing a tensile stress state across the surface defect integral which accounted for the observed surface convexity. Acid-etching and resin-cementation had a significant impact on the development and magnitude of the transient and residual stresses in the lithium disilicate glass-ceramic investigated.
PUBLISHED
Keywords: Dentistry; Oral Biosciences; glass-ceramic; ransient and residual stresses